Design of shunt active power filter to mitigate the harmonics caused by nonlinear loads - Mohamed, Mohamed Asghaiyer (2015)
Application of non-linear electrical devices has led to a distortion in the output sine waveforms of source current and voltage. It may lead equipment (connected to it) to overheat and sometimes cause damage. This paper concentrates on the design and application of three-phase shunt active power filter (SAPF) by using p-q theory to mitigate the harmonics which are created by nonlinear loads. To obtain result for this paper, the MATLAB / Simulink was used as a simulation tool. The achieved results are within the recommended IEEE-519 standard i.e. less than 5% and also the power factor (PF) of the system to almost unity.